2008
DOI: 10.1073/pnas.0807952105
|View full text |Cite
|
Sign up to set email alerts
|

Ozone production by amino acids contributes to killing of bacteria

Abstract: Reactive oxygen species produced by phagocytosing neutrophils are essential for innate host defense against invading microbes. Previous observations revealed that antibody-catalyzed ozone formation by human neutrophils contributed to the killing of bacteria. In this study, we discovered that 4 amino acids themselves were able to catalyze the production of an oxidant with the chemical signature of ozone from singlet oxygen in the wateroxidation pathway, at comparable level to antibodies. The resultant oxidant w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 27 publications
1
54
0
1
Order By: Relevance
“…These results also suggest that an oxidant with the chemical signature of ozone produced by neutrophils might potentiate a host defence system, when the host is challenged by high doses of infectious agents. These findings provide biological insights into the killing of bacteria by neutrophils (Yamashita et al, 2008). From a different point of view, it is believed that ROI function as second messengers (Hitchon & El-Gabalawy, 2004).…”
Section: Oxidative Metabolism Of Neutrophilsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results also suggest that an oxidant with the chemical signature of ozone produced by neutrophils might potentiate a host defence system, when the host is challenged by high doses of infectious agents. These findings provide biological insights into the killing of bacteria by neutrophils (Yamashita et al, 2008). From a different point of view, it is believed that ROI function as second messengers (Hitchon & El-Gabalawy, 2004).…”
Section: Oxidative Metabolism Of Neutrophilsmentioning
confidence: 99%
“…These observations suggest that alternative pathways may exist for biological killing of bacteria that are mediated by potent oxidants previously unknown to biology (Wentworth et al, 2002). More recently (Yamashita et al, 2008), it was discovered that four amino acids themselves (tryptophan, methionine, cysteine and histidine) are able to catalyze the production of an oxidant with the chemical signature of ozone from singlet oxygen in the water-oxidation pathway. The resultant oxidant with the chemical signature of ozone exhibited significant bactericidal activity in human neutrophils.…”
Section: Oxidative Metabolism Of Neutrophilsmentioning
confidence: 99%
“…The latter reaction is extremely facile under aqueous conditions [16] an antibody molecule were consumed, this could not account for the >500 mole equivalents of H 2 O 2 generated [14]. Curiously, however, Yamashita et al [17] found that out of 19 amino acids tested (excluding tyrosine), the photooxidizable amino acids methionine, cysteine, histidine, and tryptophan catalyzed the formation of ozone in the presence of singlet oxygen, comparably to antibodies, and that peptides lacking these amino acids did not generate ozone. They postulated that the amino acids catalyzed ozone formation through the water oxidation pathway but did not propose how the amino acids performed the catalysis.…”
Section: Omentioning
confidence: 99%
“…The common feature of the four amino acids that catalyze ozone formation [17] is that they are photooxidizable [14], and numerous studies have documented their oxidation by singlet oxygen under physiologically relevant conditions, both in the free form and as components of proteins [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Evidence That the Oxidation Of Amino Acids And Other Organicmentioning
confidence: 99%
“…Clearly, the combination of oxidative and nitrative responses observed in the systemic vasculature of O 3 -exposed mice does not bode well for their (or our) cardiovascular health! It is tempting to speculate that there might even be amplified rates of inflammatory cell-derived endogenous O 3 generation occurring in the systemic vascular compartment, based on recent reports of amino acid, antibody, and leukocyte-dependent oxidation of water to O 3 by singlet oxygen (24,26). This speculation, while elevated by the attractive symmetry wherein O 3 -induced responses could beget endogenous generation of O 3 , lacks traction.…”
mentioning
confidence: 99%